UPAYA MENINGKATKAN RASA PERCAYA DIRI PADA PESERTA DIDIK MELALUI PEMBELAJARAN OUTDOOR EDUCATION - Ismail Roihatul janah, - (2020)
The purpose of this study departs from problems in schools regarding students' lack of confidence in carrying out PJOK practices in the field. Researchers conducted research through the Hiking Education Outdoor Education program as the treatment and Pre-test Post-test as the beginning of the study and the end of the study after the treatment. The method used in this research is the experimental method. The population used is the seventh grade junior high school students at SMP Negeri 29 Bandung. The sample used uses technical (purposive sampling). The data collection technique or instrument used in this study was a questionnaire. These results are viewed from the final results which show no significance, it can be seen the significance value in the pre-test and post-test scores of students' confidence in the experimental group 0.20 and the control group 0.40. Thus H˳ is accepted, the result is that there is no significant effect between the value of the experimental group and the value of the confidence control of students of SMP Negeri 29 Bandung who take part in Outdoor Education. So the conclusion is that Outdoor Education has no significant effect on student confidence. Suggestions submitted in this study, need to be done with a long time and gradually tiered / developing.